Strategy for Sustainable Growth of SPA Clusters Based on the Elements of Network Interaction - OBORIN, Matvey S.; OSIPOV, Vladimir S.; SKRYL, Tatiana V. (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018, 2019)
Based on theoretical developments of leading scientists it is proposed to consider the cluster as a form of network interaction. Since the cluster is an instrument of regional economic policy, the authors consider its contribution to regional economic development. Particular attention is paid to the consideration of spa clusters, the peculiarities of health resort activity and its role for the economic development of the region. Analysing the structure of the SPA cluster, the authors propose to allocate the basic enterprises of the spa cluster, infrastructure enterprises, auxiliary institutions (universities, research centres, etc.), as well as stable links between them in the form of functions, forms of cooperation and interaction models. The article presents statistical data on the development of cluster programs in the South of Russia, which concluded that the more popular the recreational site located on the territory of the cluster and the older it is, the more financial investments the whole cluster requires. The article notes that network forms of interaction in the SPA cluster displace the traditional forms of relations in the industry. In the development of the regions of the Russian Federation, in which the resort and recreational specialization the demand for cluster and network approaches is in great demand. The existence of state programs for the formation of cluster-type resorts is explained by a combination of commercial advantages with the ability to control the targeted use of resources and the definition of owners of construction projects at the initial stages of implementation. SPA clusters contribute to the achievement of a comprehensive effect not only for the industry, but also social and economic development of the territories, improving the living conditions of the population through improving the competitiveness and quality of medical and health services.